Metode AHP Dan Topsis Diagnosa Kerusakan Sistem Pengereman Mobil Toyota Cempaka Padang Berbasis Web - Saputra, Ade (Jurnal Sains Informatika Terapan, 2024)
This study describes the design of an expert system using AHP and Topsis methods to diagnose Toyota car brakes supported with MySQL database and PHP programming language. From the research carried out at Cempaka Mobilindo Padang it can be concluded that the old system used is ineffective due to the processes that are carried out taking time and space, thus making the performance of employees less efficient. After conducting research on Cempaka Mobilindo Padang by collecting data using interview methods and other methods, it can be concluded that the information system used is still not optimal. Hence the design of the ouput design, input design, file design and program flow of the new system are carried out. The results of the analysis are applied into an expert system application program. The newly designed information system is expected to improve information quality and performance in the future